Improvement of Theoretical and Methodological Bases of Periodization of the History of Uzbek Pedagogy - Salaev, M.S.; Khaydarov, M.E. (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the improvement of the theoretical and methodological foundations of periodization of the history of Uzbek pedagogy, which makes it possible to take into account the national characteristics of the people in the process of training and education of the younger generation. Periodization of the history of pedagogy requires a description not only of the political and historical situation of any period, but also of the content, nature, and features of the pedagogical heritage. In the periodization of the history of pedagogy, pedagogical views, ideas, approaches put forward at a certain stage of historical development are analyzed. Studying the content of pedagogical thought inherent in each period, its analysis and generalization provide an opportunity for an objective periodization of the history of pedagogy and the ef ective use of advanced ideas in the system of modern education.